Euphemism of taboo translation in the Big Little Lies Series - Rita Lestari; Adi Sutrisno (Universitas Mulawarman, 2023)
To maintain cultural conformity and moral standards and ensure the target language can receive the message. Translators often use translation strategies that replace or disguise taboo words with more neutral and polite expressions to express the same message. Therefore, this study attempts to identify translation strategies and the implications of using those strategies. This study uses a qualitative descriptive method with the data source